PENERAPAN MEDIA PEMBELAJARAN MAGIC BOX UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS II DI SD NEGERI 38 PRABUMULIH - Novicha Salsabilla; Romli; Emilia Fitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was driven by the low creativity level of second-grade students at SD Negeri 38 Prabumulih, as indicated by monotonous learning processes, limited chances for students to show their imagination, and the suboptimal use of learning media that stimulate creativity. This study aimed to determine the level of students’ creativity before and after the implementation of the Magic Box learning media and to examine whether there was a significant difference after its application in Islamic Education, specifically on the topic of Angels of Allah. A quantitative approach was adopted in this study, applying a pre-experimental design that incorporated a one-group pretest-posttest model. The sample consisted of 56 second-grade students selected using a total sampling technique. Research data were collected by observation, a creativity questionnaire consisting of 20 items, documentation, and semi-structured interviews. Data analysis techniques included validity testing, reliability testing (Cronbach’s Alpha), normality testing (Shapiro-Wilk), and hypothesis testing using the Paired Sample t-Test with the assistance of SPSS software. The results showed that the average creativity score of students before the implementation of the media (pretest) was 36.95, categorized as low. After the implementation of the Magic Box media, the average creativity score (posttest) increased to 71.63, with an improvement of 34.68 points. The paired samples t-test yielded a significance value (Sig. 2-tailed) below 0.001, which falls under the 0.05 threshold, thereby confirming a statistically significant disparity between pretest and posttest scores. Therefore, it can be concluded that the implementation of Magic Box learning media is effective in improving the creativity of second-grade students at SD Negeri 38 Prabumulih